Phytochemical Screening and Biological Evaluations of Garcinia atroviridis: Phytochemical and biological evaluations of G. atroviridis - Tan, Wen-Nee; Khairuddean, Melati; Khaw, Kooi-Yeong; Vikneswaran, Murugaiyah; Yenn, Tong Woei; Ring, Leong Chean; Ibrahim, Darah (Iranian Journal of Pharmaceutical Sciences, 2019)
Garcinia atroviridis (Clusiaceae) has been used as a postpartum medication agent in folkloric medicine. However, its biological potential has not been fully evaluated. The present study was aimed to evaluate the antioxidant efficacies, cholinesterase enzyme inhibitory and antimicrobial activity of the stem bark extracts of G.atroviridis. Successive extraction was done using solvents of varied polarity. The antimicrobial activity was performed using the disc diffusion method by determining the inhibition zone and further evaluated for their minimum inhibition concentration (MIC) and minimum lethal concentration (MLC). Anti-cholinesterase activity was determined by spectrophotometric method while antioxidant activity was evaluated by DPPH radical scavenging. The extracts showed significant inhibitory activity against food borne bacteria. However, only dichloromethane extract exhibited the anti-yeast potential against Candida utilis and none of the extracts tested showed anti-fungi activity. For cholinesterase enzyme inhibitory activity, ethyl acetate extract exhibited the strongest acetylcholinesterase (AChE) inhibitory activity with an IC50 value of 5.46 ± 2.91 μg/mL while water extract showed the lowest IC50 value (29.31 μg/mL) against butyrlcholinesterase (BChE). For antioxidant activity, methanol extract showed moderate activity against DPPH radicals with EC50 value of 71.96 μg/mL.The dichloromethane extract exhibited significant antimicrobial activity while ethyl acetate showed the strongest acetylcholinesterase (AChE) inhibitory activity. The present study showed the significance of this commercial plant as the potential source of bioactive compounds.